PEMBERIAN JENIS PAKAN BERBEDA TERHADAP PERTUMBUHAN IKAN SELAIS (Kryptopterus lais) DI PERAIRAN TASIK BETUNG SUNGAI MANDAU - Rosyadi Rosyadi; Agusnimar Agusnimar (UIR Press, 2016)
The study aims to determine the feeding of different products on the growth of the fish slice. Culture vessel in the form of net bags of 1 x 1 x 1.2 (m) of 9 bags with stocking density 20 birds. The method used experiment with completely randomized design (CRD), three treatments and three looping. Such treatment is P1 = Feeding Comfeed products, P2 = Feeding Sun products, and P3 = Feeding Charoen Pokphand products. From the results of research feeding with different products derived growth to slice fish weight of 17.23 grams P1, P2 was 19.26 grams, and P3 of 17.83 gr. The growth of the fish slice length of 4.13 cm for P1, P2 and P3 of 5.30 cm is 27 cm. The growth rate of daily weight of the fish slice to P1sebesar 2.13%, with a value of 2.27% P2 and P3 of 2.19%. Slice fish mortality during the study for as many as 1 tail P1, P2 and P3 2 tails as much as 1 tail. For all three types of feed of different products is not a significant effect on the growth of the fish slice. Water quality parameters for such a study, the water temperature ranges from 25-28 ° C, acidity (pH) of 5-8, dissolved oxygen (DO) between 5.97 to 6.38 ppm, and ammonia (NH3) between 0.19 - 0.32 ppm. Value parameter water quality of Lake Betung waters during the study still supports for the life and growth of fish slice.